2016
DOI: 10.1101/gr.203216.115
|View full text |Cite
|
Sign up to set email alerts
|

Transmission of human mtDNA heteroplasmy in the Genome of the Netherlands families: support for a variable-size bottleneck

Abstract: Although previous studies have documented a bottleneck in the transmission of mtDNA genomes from mothers to offspring, several aspects remain unclear, including the size and nature of the bottleneck. Here, we analyze the dynamics of mtDNA heteroplasmy transmission in the Genomes of the Netherlands (GoNL) data, which consists of complete mtDNA genome sequences from 228 trios, eight dizygotic (DZ) twin quartets, and 10 monozygotic (MZ) twin quartets. Using a minor allele frequency (MAF) threshold of 2%, we ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
85
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(103 citation statements)
references
References 56 publications
11
85
4
Order By: Relevance
“…This may seem to contradict previous observations that heteroplasmies become more numerous with age (e.g., Rebolledo-Jaramillo et al, 2014; Li et al, 2016). If the effective population size of the somatic stem cells supporting mitotic somatic tissues is larger than the effective population size during embryogenesis or the maternal germ line, an accumulation of genetic drift with age would produce additional de novo somatic heteroplasmies.…”
Section: Discussioncontrasting
confidence: 55%
“…This may seem to contradict previous observations that heteroplasmies become more numerous with age (e.g., Rebolledo-Jaramillo et al, 2014; Li et al, 2016). If the effective population size of the somatic stem cells supporting mitotic somatic tissues is larger than the effective population size during embryogenesis or the maternal germ line, an accumulation of genetic drift with age would produce additional de novo somatic heteroplasmies.…”
Section: Discussioncontrasting
confidence: 55%
“…As far as the germline is concerned, the abrupt enrichment of one genotype over the other have been recognized as the mtDNA bottleneck effect since a seminal work in heteroplasmic cows (Hauswirth and Laipis, 1982). More recently, extensive population studies on human mother/offspring pairs showed a significant number of cases where a genotype that was not detectable in the mother showed up as significant heteroplasmy in the child (Rebolledo-Jaramillo et al, 2014), (Li et al, 2016). This implies that a rare genotype, perhaps a nascent mutant molecule, in some cases may enjoy a dramatic enrichment among germline mitochondria in normal humans within a one generation time frame.…”
Section: Note 3: Functional Diploidy Of Spermatozoa: Mendelian Segregmentioning
confidence: 99%
“…In particular, for certain ontogenetic processes, we model the rate of accumulation of genetic drift and mutation with age. This is motivated by previous observations that heteroplasmic variants segregate and accumulate with time within somatic tissues (Li et al, 2015;Sondheimer et al, 2011;Rebolledo-Jaramillo et al, 2014) and within the germline (Rebolledo-Jaramillo et al, 2014;Li et al, 2016;Wachsmuth et al, 2016). Finally, in the typical population-phylogenetic model, each branch of the phylogeny represents a single period in evolutionary history and is modeled by a single parameter.…”
Section: Ontogenetic Phylogeniesmentioning
confidence: 99%
“…While it was long thought that the mitochondria within the human body are genetic clones, it is now recognized that variation of mitochondrial DNA (mtDNA) is common within human cells and tissues. This variation, termed mitochondrial heteroplasmy, is a normal part of healthy human biology (Rebolledo-Jaramillo et al, 2014;Li et al, 2016Li et al, , 2010, but it is also important in human health and disease, being the primary mode of inheritance of mitochondrial disease and playing a role in cancer and aging (reviewed in Stewart and Chinnery, 2015;Wallace and Chalkia, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation